Атлас мира: страны мира в картах и цифрах / [главный редактор Т. П. Сидоренкова] - Сидоренкова Т. П. (АСТ-Пресс, 1999)
Экземпляры: ЦБ (2000 г.) / Инвентарный номер: 33261 / Цена: 35.00 / Авт.знак: А 92 / ГРНТИ: 39.19 / ББК: 26.82